"Stiamo lavorando per voi": per una maggiore collaborazione tra filologi e storici della lingua italiana - Larson, Pär (Verbum – Analecta Neolatina, 2002)
"We are working for you" - During the second half of the XXth century, numerous linguistical studies of Old Italian non-literary texts have appeared. These works aim to reconstruct the state of the spoken language in the differents parts of the peninsula and would therefore seem to be obligatory reading for critical editors of literary texts of the same regions, but this is not always the case. This paper examines a number of cases in which otherwise sound scholars have come a cropper from not using the relevant linguistic research literature.